Modeling of the Learning Process in Adaptive Training Complexes - Obukhov, Artem Dmitrievich; Krasnyansky, Mikhail Nikolaevich; Dedov, Denis Leonidovich; Siukhin, Alexander Andreevich (Journal of Applied Engineering Science, 2018)
The article is devoted to the solving of increasing of the effectiveness of training in adaptive training complexes due to individualization of learning process, adaptation for psychological, physical, physiological, anthropometrical and intellectual features of each person. The questions of modeling of learning process in training systems and its study, formalization and software realization are considered. The task of learning process organization in adaptive training complexes (ATC) by optimal way in accordance with selected criteria is stated on the base of developed mathematical model considering the individual features of learners. Using the available approaches to modeling of learning process, we adjusted the psychological, intellectual, physical, physiological and anthropometric metrics concepts, the complexity of the problem is solved. The described statement of a problem of learning process organization, criteria of optimization and mathematical model allow choosing the most suitable forms of studying, methodic, software and hardware tools for learning process on the stage of learning techniques design. The obtained scientific results can be used both at the stage of learning systems design and at the stages of their functioning for the aims of efficiency of
Keywords: Adaptive training complexes; Qualimetric competence scale; re-adaptation; Learning